ANALISIS EFISIENSI PRODUKSI KOMODITAS KAPAS DI SULAWESI SELATAN - AMIRUDDIN SYAM (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
The end target of development policy on plantation is to increase its product export rate aswell as to supply sufficiently its domestic industry needs. It could be achieved by increasingits productivity and enhancing its production efficiency. The objective of this research is tostudy cotton-farming performance in order to collect its input-output data, the function of thecotton production data including its production possibility frontier, and too see whichvariable might influence the production function. The result shows that the TE (TechnicalEfficiency) average for sampled cotton farmers is 0.70 in normal distribution. The applicationof the new technology on the transgenic molecular cotton and cooperation with operatingcompany are likely able to give the farmers prospective alternative in the future as it gives agreater benefit than that one they earned previously by planting local variety cotton. Thisreason is supported by sensitivity analyses in which if the cottonseeds price is reduced thenthe farmers are still benefited. The transgenic cottonseed has better germination rate andviability as well as higher quality and quality of its harvested production. These results couldbe achieved only if all the physical agronomic requirements such as favorable agro-climateduring vegetative stage are met adequately in addition to proper recommended fertilizing.